THE AKUT TOXICITY TESTING LETHAL DOSE ORAL GREEN MENIRAN LEAF EXTRACT BY USING MICE - Ni Kadek Eka Widiadnyani; Luh Made Sudimartini (Buletin Veteriner Udayana, 2024)
The use of a dose limit of green meniran leaf extract (Phylanthus niruri Linn) must be known for its safety which is supported by research results. The aims of this research to determine the acute lethal dose (LD50) toxicity and to examine the macropathological changes in the vital organs of mice. A total of 30 male mice and 30 female mice were divided into five groups and six replicates. Experimental mice in the control group (K) were given 0.9% NaCl, while those given meniran extract at doses of 50, 300, 2000 and 5000mg/KgBW were grouped as treatments. The preparation was given orally once and then the observations were made in the first 30 minutes after giving the preparation and periodically every 4 hours for the first 24 hours and once a day then the mice were observed for clinical symptoms, mortality and body weight. At the end of the study (day 14), the experimental mice were sacrificed for macropathological evaluation. giving meniran extract orally up to a dose of 5000 for 14 days did not cause death or showed toxic symptoms and normal growth. On macropathological examination of size, color and consistency, all organs were in normal condition. Green meniran leaf extract preparations > 5000 mg/kgBW are practically non-toxic and didn’t cause organ abnormalities. It is necessary to do research on toxicity, biocompatibility, effects, and potential for subchronic toxicity to changes in histopathological structure with a longer study duration, higher doses and more varied dosage ranges.